Integrity of Actin-Network Is Involved in Uridine 5'-Triphosphate Evoked Store-Operated CaM2+ Entry in Bovine Adrenocortical Fasciculata Cells - Kawamura Masahiro; Osamu Terasaka; Takanori Ebisawa; Ichiro Kondo; Eiji Masaki; Ashram Ahmed; Miyuki Kagata (Elsevier, 2003)
Store-operated Ca2+ entry channels (SOCs) play an important role in the regulation of diverse non-excitable cell functions. However, the precise mechanism of SOCs activation is still controversial. Uridine 5'-triphosphate (UTP) was shown to induce Ca2+ entry in a dihydropyridines-insensitive manner and accelerated steroidogenesis in bovine adrenocortical fasciculata cells (BAFCs) via the Gq/11 protein-coupled P2Y2 receptor. Therefore we investigated whether UTP is involved in SOCs activation and the mechanism of UTP-induced SOCs activation. Fura 2-loaded BAFCs were used for the measurement of intracellular concentration of Ca2+ ([Ca2+]i) mobilization. Extracellular UTP evoked Ca2+ release from intracellular stores followed by an increase in Ca2+ entry. The Ca2+ influx elicited by UTP was inhibited not by nifedipine, but by Zn2+, Cd2+, and Ni2+ (potency order: Zn2+ > Cd2+ >> Ni2+), and the effect of UTP was also attenuated by a phospholipase C inhibitor (U73122). These results indicate that UTP activates SOCs in BAFCs. The increase in [Ca2+]i by UTP was attenuated by ML-9, a myosin-light chain kinase inhibitor, and calmodulin inhibitors, W-7 and E6 berbamine, in a concentration-dependent manner. These reagents depolymerized actin filaments with rhodamine staining in BAFCs. Cytochalasin D also inhibited UTP-activated SOCs and depolymerized actin filaments. From these results, we proposed that calcium/calmodulin dependent myosin-light chain kinase is involved in the mobilization of actin filaments and the integrity of actin-network plays an important role in UTP-induced SOCs activation in BAFCs.